Energy harnessing of multiple semi-active flapping ellipses in V-shape formation - Gong, Lingyun (2023)
Two-dimensional numerical simulations based on an immersed boundary method are performed for the two-foil system with varying spacings, and a staggered arrangement with a spacing normalized by chord length (X d / D, Y d / D) = (2.0, 2.5) is found to be the most favorable for energy harnessing with the efficiency enhancement of nearly 40% for the downstream foil. By scrutinizing the mean flow characteristics and the instantaneous wake dynamics, it is revealed that convective flow acceleration and vortex impingement in synchronized timing with foil motion are the two primary mechanisms that contribute to significant efficiency improvement. Based on the staggered arrangement for the two-foil system, a V-shape formation is further proposed for the multiple-foil system and verified with the highest efficiency of energy harnessing up to nearly twice that of a single foil.